TINGKAT KETERAMPILAN TEHNIK DASAR SEPAKBOLA TIM LPI MAHASISWA UNSRI TAHUN 2012 - Reza Resah Pratama (Universitas Sriwijaya, 2017)
Abstract: The aim of this research is to know the skill level of basic football technique of LPI Student Team Unsri Year 2012. This research method used is descriptive method, by collecting data using the basic technique of soccer test with the result of skill test of soccer technique LPI student team Unsri best score and lowest basic technique skill football: best short passing 7.13 s, 8.10 sec and less 8.22 sec. Best dribling 1.40 s, medium 2.10 s and less 2.50 s. Running With the ball best 1.08 sec, medium 2.38 sec and less 2.58 sec. Best heading 6.2m, medium 5.4m and less 4.5m. Shoting best 55, moderate 40 and less 30. Thow In best 13m, medium 11m and less 8m. The population in this study were students who joined the Student Units LPI Team Year 2012 which amounted to 20 players, taking data through skill test using descriptive method. Keywords: Basic Techniques, Skills and Football